Ethical Justification for Deferral of Consent in the AcT Trial for Acute Ischemic Stroke. Issue 7 (23rd May 2022) - Faris, Hannah; Dewar, Brian; Dowlatshahi, Dar; Ramji, Alnar; Kenney, Carol; Page, Stacey; Buck, Brian; Hill, Michael D.; Coutts, Shelagh B.; Almekhlafi, Mohammed; Sajobi, Tolulope; Singh, Nishita; et al.
Abstract : The AcT trial (Alteplase Compared to Tenecteplase) compares alteplase or tenecteplase for patients with acute ischemic stroke. All eligible patients are enrolled by deferral of consent. Although the use of deferral of consent in the AcT trial meets the requirements of Canadian policy, we sought to provide a more explicit and rigorous approach to the justification of deferral of consent organized around 3 questions. Ultimately, the approach we outline here could become the foundation for a general justification for deferral of consent.